2012
DOI: 10.2340/00015555-1364
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Modulation of Facial Itch- and Pain-related Responses and Grooming Behavior in Rats

Abstract: Intradermal facial injections of pruritogens or algogens elicit distinct behavioral hindlimb scratch or forelimb wiping responses in rodents. We systematically investigated the parameters and opioid modulation of these evoked behaviors and spontaneous facial grooming in rats. Serotonin (5-HT) elicited hindlimb scratch bouts with few wipes. Scratching was attenuated by the µ-opiate antagonist naltrexone but not morphine. In contrast, cheek injection of mustard oil (allyl-isothiocyanate (AITC)) elicited ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…We show that naloxone reduces the number of scratch bouts elicited by serotonin, a finding which has been previously shown for opioid receptor antagonists naloxone (Hachisuka et al, 2010) and naltrexone (Spradley et al, 2012). μ-Opioid receptor antagonists have been used to reduce itch produced by several pruritogens in a variety of human conditions (Phan et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We show that naloxone reduces the number of scratch bouts elicited by serotonin, a finding which has been previously shown for opioid receptor antagonists naloxone (Hachisuka et al, 2010) and naltrexone (Spradley et al, 2012). μ-Opioid receptor antagonists have been used to reduce itch produced by several pruritogens in a variety of human conditions (Phan et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…Both behaviors were directed to the site of injection. This distinction between itch-evoked scratching and pain-evoked wiping has been replicated using an array of other pruritogens and algogens in mice (Akiyama et al, 2010; Wilson et al, 2011) and rats (Klein et al, 2011; Spradley et al, 2012). …”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Intraplantar injection of capsaicin elicited licking behavior in rats (Klein et al, 2011a), and hindpaw injection of formalin elicited licking in mice (Hagiwara et al, 1999). We previously reported that systemic administration of morphine suppressed forelimb wiping, but not hindlimb scratching, elicited by id cheek injections of capsaicin or mustard oil in mice and rats, consistent with the notion that forelimb wiping reflects pain (Akiyama et al, 2010c; Spradley et al, 2012a). Presumably, licking of the hindpaw or forelimb wiping directed to the cheek represent the biomechanically available nocifensive responses to ameliorate chemogenic pain in these two different body areas.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, LaMotte’s group (119) modified the traditional model to establish the “cheek injection model.” They reported that mice exhibit distinct behaviors in response to cheek injection of pruritogens versus algogens: Pruritogens elicit scratching with the hind paw, whereas algogens evoke facial wiping with the forelimb. This model was amended in rats by Carstens’ group (127) and provides a reliable means of distinguishing itch and pain behaviors.…”
Section: Animal Models For Investigating Itch Mechanismsmentioning
confidence: 99%